Estrogen receptor alpha, g-protein coupled estrogen receptor 1, and aromatase: developmental, sex, and region-specific differences across the rat caudate-putamen, nucleus accumbens core and shell - Krentzel, Amanda A. (J Comp Neurol, 2020)
Sex steroid hormones such as 17β-estradiol (estradiol) regulate neuronal function by binding to estrogen receptors (ERs), including ERα and GPER1, and through differential production via the enzyme aromatase. ERs and aromatase are expressed across the nervous system, including in the striatal brain regions. These regions, comprising the nucleus accumbens core, shell, and caudate-putamen, are instrumental for a wide-range of functions and disorders that show sex differences in phenotype and/or incidence. Sex-specific estrogen action is an integral component for generating these sex differences. A distinctive feature of the striatal regions is that in adulthood neurons exclusively express membrane but not nuclear ERs. This long-standing finding dominates models of estrogen action in striatal regions. However, the developmental etiology of ER and aromatase cellular expression in female and male striatum is unknown. This omission in knowledge is important to address, as developmental stage influences cellular estrogenic mechanisms. Thus, ERα, GPER1, and aromatase cellular immunoreactivity was assessed in perinatal, pre-pubertal, and adult female and male rats. We tested the hypothesis that ERα, GPER1, and aromatase exhibits sex, region, and age-specific differences, including nuclear expression. ERα exhibits nuclear expression in all three striatal regions before adulthood and disappears in a region- and sex-specific time-course. Cellular GPER1 expression decreases during development in a region- but not sex-specific time-course, resulting in extranuclear expression by adulthood. Somatic aromatase expression presents at pre-puberty and increases by adulthood in a region- but not sex-specific time-course. These data indicate that developmental period exerts critical sex-specific influences on striatal cellular estrogenic mechanisms.